Determinan terhadap profitabilitas dengan kredit bermasalah sebagai pemoderasi pada bank umum konvensional - Larashati, Adinda; Badjuri, Achmad (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of liquidity ratios and efficiency ratios on profitability with the ratio of non-performing loans as a moderating variable. This research was conducted at conventional commercial banks listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period using purposive sampling with several criteria. The data used is secondary data. The number of samples selected was 128 with a period of 3 years. The data analysis technique used is Moderated Regression Analysis (MRA). The results showed that the liquidity ratio had a significant positive effect on profitability while the efficiency ratio had no significant effect on profitability. Non-performing loans can moderate the ratio of liquidity to profitability while non-performing loans cannot moderate the ratio of efficiency to profitability.